2011
DOI: 10.1021/jp108565x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Capture of Phosphine by a Sol−Gel-Derived Cu/TiO2 Adsorbent − Interaction Mechanisms

Abstract: In this study, a novel sol-gel-derived Cu/TiO 2 adsorbent has been demonstrated to exhibit exceptional capacities of 40.62, 49.52, and 108.48 mg PH 3 /g Cu/TiO 2 for the oxidative capture of phosphine (PH 3 ) in N 2 , air, and humidified air, respectively. We have proposed the oxidative mechanisms for PH 3 on the Cu/TiO 2 sample on the basis of elemental, chemical state, functional group, and microstructural analysis. Moreover, the influence of O 2 and water vapor on the capture capacity is discussed. The tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…As shown in Figure and Table , three P 2p photoelectron lines centered at 129.12, 132.8, and 134.1 eV were obtained after adsorption, which represent P – , P 3+ , and P 5+ , respectively . Likewise, only P 5+ including 95.7% P 2 O 5 and 4.3% H 3 PO 4 was found on Cu/γ-Al 2 O 3 after total oxidation in ambient air.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…As shown in Figure and Table , three P 2p photoelectron lines centered at 129.12, 132.8, and 134.1 eV were obtained after adsorption, which represent P – , P 3+ , and P 5+ , respectively . Likewise, only P 5+ including 95.7% P 2 O 5 and 4.3% H 3 PO 4 was found on Cu/γ-Al 2 O 3 after total oxidation in ambient air.…”
Section: Resultsmentioning
confidence: 87%
“…As shown in Figure 15 and Table 4, three P 2p photoelectron lines centered at 129.12, 132.8, and 134.1 eV were obtained after adsorption, which represent P − , P 3+ , and P 5+ , respectively. 33 Likewise, only P 5+ including 95.7% P 2 O 5 and 4.3% H 3 PO 4 was found on Cu/γ-Al 2 O 3 after total oxidation in ambient air. This further confirmed that the chemical adsorption is rather accomplished by redox and reduction reaction rather than the simple reaction we estimated before.…”
Section: Influence Of Hydrogen Chloridementioning
confidence: 86%
See 1 more Smart Citation
“…What's more, the obvious peak between 940 and 945 eV is identified as the satellite peak of Cu 2+ . It is reported that CuQDs surface is not evitable to be partially oxidized into CuO and Cu(OH) 2 while exposed to ambient air . Besides, XPS is used for surface analysis, while XRD is for bulk analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The result shows that the MWSAC adsorbent owns the biggest PH 3 breakthrough adsorption capacity and is one of the candidates for PH 3 adsorption removal from yellow phosphorus tail gas. Table 5 (2,4,7,19,22,24,(35)(36)(37) shows that some of the promising experimental performances were obtained with different composite adsorbents. In order to improve PH 3 adsorption capacity, most of the adsorbents are modified by copper (Cu).…”
Section: Ph 3 Adsorption Performance Comparisonmentioning
confidence: 98%